Customer Satisfaction Sebagai Variabel Moderasi Hubungan Customer Experience Dan Customer Value Terhadap Customer Loyalty Pada Produk Parfum Saff & Co Di Tiktok Shop - Nugroho, Rigel Rizky Dwi; Anomsari, Ariati; Sari, Raden Ayu Aminah Rizkia Puspita; Farida, Ida (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
This study aims to evaluate the influence of customer experience and customer value on customer loyalty, with customer satisfaction as a mediating variable. The research employs a quantitative explanatory survey approach by distributing questionnaires as the data collection technique. The sampling method used is purposive sampling, applying Hair's formula, resulting in a sample of 120 respondents, including consumers of Saff&Co perfume products on TikTok Shop. Data analysis is conducted using Smart PLS software version 4. The results indicate that customer experience has a positive and significant effect on customer loyalty, and customer loyalty positively and significantly influences customer satisfaction. Additionally, customer satisfaction mediates the relationship between customer experience, customer value, and customer loyalty. However, customer value does not significantly affect customer loyalty, nor do customer experience and customer value significantly influence customer satisfaction